Bacteria Cellulose: Biopolymer from Gluconacetobacter Xylinus. Issue 1 (January 2015) - Mathur, Garima; Dua, Aarushi; Das, Anushuya Raj; Kaur, Harleen; Kukal, Samiksha; Sharma, Parul; Goswami, Navendu; Sahai, Anshuman; Mathur, Ashwani; Bhattacharya, Bhaskar
Summary Summary In the present study, production, characterization and optimization of bacterial cellulose (BC) from Gluconacetobacter xylinus MTCC 7795 has been investigated. Effect of various carbon sources and bioprocess parameters on bacterial growth rate and subsequent BC production were studied and optimized. Supplementation of the media with different carbon sources resulted in varying yield of bacterial cellulose. Variations in the arrangement of bacterial cellulose with variations in carbon source were analyzed using FT‐IR. Results have suggested that characteristic vibrational modes of BC produced were almost same in the typical fingerprint regions as in commercial cellulose.